On The Problems of Formation of Musical Thinking at Young People - Odina, Sharipova (European Journal of Life Safety and Stability (2660-9630), 2022)
The article reveals the scientific significance of the patterns of formation and development of musical thinking of students. At the same time, it is emphasized to create a modern basis for the conditions, opportunities, methods and means of educating a harmoniously developed generation of musical thinking.